A guy goes into a bar ... : 501 bar jokes, stories, anecdotes, quips, quotes, riddles, and wisecraks /: 501 bar jokes, stories, anecdotes, quips, quotes, riddles, and wisecraks. (©2005) - Unknown
No abstract available